2009
DOI: 10.1055/s-0029-1185684
|View full text |Cite
|
Sign up to set email alerts
|

Three New Naphthoquinone Pigments Isolated from the Freshwater Fungus,Astrosphaeriella papuana

Abstract: Three new naphthoquinones, astropaquinones A-C (1-3), were isolated from cultures of the freshwater fungus Astrosphaeriella papuana YMF 1.01181, together with the known compound, 6-hydroxy-2,4-dimethoxy-7-methylanthraquinone (4). The structures of the compounds were settled mainly by interpretation of their 1D and 2D NMR spectra. Astropaquinone B (2) and C (3) were found to possess a rare pyranonaphthoquinone skeleton containing a lactol ring. Furthermore, compounds 1-4 showed moderate antagonistic activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…and Escherichia coli; further, 170 was active against Colletotrichum sp., Fusarium sp., Giberella saubinetii, and Phyllosticta sp. (Wang et al 2009). …”
Section: Helicodendron Giganteummentioning
confidence: 93%
“…and Escherichia coli; further, 170 was active against Colletotrichum sp., Fusarium sp., Giberella saubinetii, and Phyllosticta sp. (Wang et al 2009). …”
Section: Helicodendron Giganteummentioning
confidence: 93%
“…Heptaketides are a subgroup of polyketides showing diverse structural features and biological effects. To date, a variety of heptaketides including pyranonaphthoquinones, [1][2][3] naphthoquinones, 4 and other rearranged, 5 ring-opened, 6,7 or dimeric 8 derivatives, have been encountered as fungal secondary metabolites, and showed a broad spectrum of biological activities, such as antibacterial, antifungal, and antitumor effects. [1][2][3][4] Natural products incorporating a quinone moiety have been the subject of intensive investigations due to their potent antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the literature revealed that 2 was identical in all aspects, expect for the specific rotation {[α] 18 D −45 (c 0.04, CHCl 3 )}, to astropaquinone B, previously isolated from the freshwater fungus Astrosphaeriella papuana. 10 The absolute configuration of astropaquinone B was assigned as (1R,3S) by total synthesis, 14 showing consistency in the specific rotations {[α] 19 D +35.0 (c 0.14, CHCl 3 )} with that of the natural isolate {[α] 27.8 D +45.1 (c 0.12, CHCl 3 )}. Because the sign of the specific rotation of 2 was opposite that of astropaquinone B, 2 is the enantiomer of astropaquinone B.…”
mentioning
confidence: 98%